A formula of spectral radius of integral Volterra operators - Zabreiko, P. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. П. Забрейко. О спектральном радиусе интегральных операторов Вольтерра P. Zabreiko. Apie integralinių Volteros operatorių spektrinį spindulį